Detection and Direction Determination of Approaching Vehicle Noises Among Older Adults. (March 2016) - Barton, Benjamin K.; Heath, Gretchen E.; Lew, Roger
We examined detection and direction determination of auditory cues from a pedestrian environment among a sample of older and younger adults. Review of relevant research suggests normal aging is associated with declines in physical, cognitive, and perceptual abilities. Relatively, few studies have examined the impact of such developmental changes on pedestrian safety among older adults, and none have examined such factors in relation to use of auditory cues. Thirty-five younger and 35 older adults completed cognitive measures and a pedestrian auditory detection task. Some results by speed were similar to past research that examined younger samples. Interactions were discovered between age and speed conditions within the auditory task. Results are discussed in the context of past research and with regard to informing future injury prevention efforts.